Poly(glycidyl methacrylate)-functionalized magnetic nanoparticles as platforms for linking functionalities, bioentities and organocatalysts. Issue 49 (3rd May 2016) - Nan, Alexandrina; Radu, Teodora; Turcu, Rodica
Abstract : Magnetic nanoparticles coated with polyglycidyl methacrylate are ring-opened by nucleophiles containing reactive centers, bioentities, organocatalysts leading to new materials. Abstract : New magnetic core shell nanoparticles were synthesized consisting of a magnetite core and a poly(glycidyl methacrylate) shell. Magnetite nanoparticles were first coated by bis(methacryloyloxyethoxy)phosphate as a reactive alkene-containing anchor followed by radical polymerization of glycidyl methacrylate. The poly(glycidyl methacrylate) coated MNPs represent versatile magnetic nano-platforms capable of linking various N-, S- and O-nucleophiles by opening the oxirane ring. In this way bioentities such as α-amino acids could be introduced directly or via first introducing a binucleophile followed by acylation (biotin) or thiol-ene click chemistry (cinchonine). Comprehensive high resolution XPS spectroscopy investigations were used as a major tool for analyzing the various types of magnetic nanoparticles. The results are attractive for application in biomedicine, organocatalysis and nanotechnology.